The effect of anaerobic exercises on electrical activity signal of the working muscles of the 50-meter freestyle junior swimmers - Muhyaddin, Tara; Najemaldeen , Eman (Journal of Physical Education, 2023)
The research aimed to identify the values of the electrical activity signal of the triceps brachii muscle, middle deltoid muscle, and latissimus dorsi muscle for the dominant side during the performance of free swimming outside the water, and to identify the differences between the pre and post-tests in peak, mean of peaks, area, and variability %. The experimental approach was used in one group design. The subject was 6 junior swimmers of Sulaimani Club. The mean heights, weights, and age were (171.17 ± 2.86 cm) (54.50 ± 5.75 kg) (15.17 ± 0.75 years), respectively. The out-of-water training device and sEMG were applied by using (Ultium EMG) and its software (MR2.12). The training was applied for (10) weeks, and the results showed significant development in the electrical activity, and the largest development occurred in the triceps brachii muscle.